2021
DOI: 10.1038/s41380-021-01359-9
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and subcortical neuroanatomical signatures of schizotypy in 3004 individuals assessed in a worldwide ENIGMA study

Abstract: Neuroanatomical abnormalities have been reported along a continuum from at-risk stages, including high schizotypy, to early and chronic psychosis. However, a comprehensive neuroanatomical mapping of schizotypy remains to be established. The authors conducted the first large-scale meta-analyses of cortical and subcortical morphometric patterns of schizotypy in healthy individuals, and compared these patterns with neuroanatomical abnormalities observed in major psychiatric disorders. The sample comprised 3004 un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 114 publications
(158 reference statements)
3
19
0
Order By: Relevance
“…We collected thirteen spatial maps of cortical abnormalities from the ENIGMA consortium for the following diseases, disorders, and conditions: 22q11.2 deletion syndrome 26 , attention-deficit/hyperactivity disorder (ADHD) 27 , autism spectrum disorder (ASD) 28 , idiopathic generalised epilepsy 29 , right temporal lobe epilepsy 29 , left temporal lobe epilepsy 29 , depression 30 , obsessive-compulsive disorder (OCD) 31 , schizophrenia 32 , bipolar disorder 33 , obesity 34 , schizotypy 35 , and Parkinson's disease 36 . For simplicity, we refer to diseases, disorders, and conditions as "disorders" throughout the text.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We collected thirteen spatial maps of cortical abnormalities from the ENIGMA consortium for the following diseases, disorders, and conditions: 22q11.2 deletion syndrome 26 , attention-deficit/hyperactivity disorder (ADHD) 27 , autism spectrum disorder (ASD) 28 , idiopathic generalised epilepsy 29 , right temporal lobe epilepsy 29 , left temporal lobe epilepsy 29 , depression 30 , obsessive-compulsive disorder (OCD) 31 , schizophrenia 32 , bipolar disorder 33 , obesity 34 , schizotypy 35 , and Parkinson's disease 36 . For simplicity, we refer to diseases, disorders, and conditions as "disorders" throughout the text.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we find a similar trend of increased connectomic influence for severity of psychotic symptoms: namely, schizotypy and schizophrenia. Although schizotypy is not an earlier stage of schizophrenia (indeed, schizotypy is not a disorder per se but rather a multidimensional continuum of traits related to psychosis), individuals with schizotypy exhibit similar, albeit attenuated, characteristics as schizophrenia patients 35 . We find that the connectomic influence is considerably greater in schizophrenia compared to schizotypy, which may suggest that the structural network gradually becomes more implicated in disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 A recent meta-analysis from the Enhancing NeuroImaging Genetics through Meta-Analysis (ENIGMA) Schizotypy working group has identified that higher schizotypy scores, assessed using different questionnaires, were associated with thicker right medial orbitofrontal/ventromedial prefrontal cortex. 15 In studies which used only the Schizotypal Personality Questionnaire (SPQ), 11, 16 increasing schizotypy levels have been inconsistently associated with smaller thalamus 17 and larger striatum (pallidum/putamen), 18 as well as thinner pars orbitalis , rostral middle frontal and parahippocampal gyri 19 and thicker right dorsolateral prefrontal cortex and dorsal premotor cortex/frontal eye fields. 17…”
Section: Introductionmentioning
confidence: 99%
“…12 A recent meta-analysis from the Enhancing NeuroImaging Genetics through Meta-Analysis (ENIGMA) Schizotypy working group has identified that higher schizotypy scores, assessed using different questionnaires, were associated with thicker right medial orbitofrontal/ventromedial prefrontal cortex. 15 In studies which used only the Schizotypal Personality Questionnaire (SPQ), 11,16 increasing schizotypy levels . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Introductionmentioning
confidence: 99%